"Go up onto a High Mountain" (Is. 40:9): Theophanic Exegesis as Mystical Ascent in On First Principles. Issue 1 (February 2020) - Allen, John J.
Origen of Alexandria's exegetical method in On First Principles draws on theophanic language to explicate the Christian interpreter's mystical ascent toward the contemplation of God through scripture. This method of theophanic exegesis seeks to move beyond the literal, "bodily" meaning of the scriptural text and reveal the hidden, "veiled" meaning. Scripture then becomes the intersection of God's outpouring gift of theophanic partaking with the exegete's morally purified gaze. Origen draws on specific theophanic encounters, such as Paul's ascension and the Transfiguration of Jesus on Mount Tabor, as well as other mystical metaphors. By uncovering Origen's approach to the "divine scriptures, " one can better appreciate his depth of faith—both moral and mystical. In this way, Origen's method of exegesis can be situated within an interpretive tradition that employs the language of theophanies and fuses scriptural exegesis with moral purification and divine encounter.